(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
This study investigates the palaeoecology of fossil perissodactyls (equids) from the late Miocene of Maragheh, northwestern Iran. We used dental micro- and mesowear techniques to draw robust inferences about fossil equid paleoenvironment. Mesowear and microwear analyses were applied to the upper molars of three species of hipparionine horses. For this purpose, we investigated samples from three fossiliferous localities: Rohanion, Azim, and Cizdahaban. Six fossil specimens were analyzed for enamel meso- and microwear and results were compared to an extensive database of extant ungulates. Results indicated overlap of the Maragheh hipparions with the dietary signal of extant grazers and grass-dominated mixed feeders. This is consistent with the supposed vegetational habitat proposed by previous mesowear studies. The different species of hipparions from Maragheh had similar diets and were consuming a mixture of plants but with a preference for grasses. These results are consistent with paleoenvironmental reconstructions of the late Miocene dominated by open grassland areas among more wooded settings.